A Meta-Analysis of the Efficacy and Toxicity of Twice-Daily vs. Once-Daily Concurrent Chemoradiotherapy for Limited-Stage Small Cell Lung Cancer Based on Randomized Controlled Trials - Wu, Qian; Xiong, Yiting; Zhang, Shujuan; Chen, Xinling; Yi, Fengming; Wei, Yiping; Zhang, Wenxiong (Frontiers in Oncology, 2020)
Background: Currently, the accepted standard management of limited-stage small cell lung cancer (SCLC) is concurrent chemoradiotherapy (CCRT), but the frequency of radiotherapy is controversial. Therefore, this meta-analysis, which compared the efficacy and toxicity between twice-daily (BID) and once-daily (OD) CCRT, was performed to help clinicians make better decisions Methods: Relevant randomized controlled trials (RCTs) were collected by searching the PubMed, Ovid MEDLINE, Embase, ScienceDirect, Web of Science, the Cochrane Library, Scopus and Google Scholar databases to assess antitumor effects (overall survival, OS; progression-free survival, PFS; overall response rate, ORR) and toxicity (adverse effects, AEs). Results: We screened 1499 articles and included 5 RCTs including 1421 patients. We found that BID CCRT improved OS (hazard ratio, HR=0.88, 95% confidence interval, CI 0.78-0.99, p=0.03), the one-year OS rate (OSR-1y, risk ratio, RR=1.07, 95%CI 1.01-1.13, p=0.03) and OSR-4y (RR=1.22, 95%CI 1.03-1.43, p=0.02), with better trends in OSR-2y, OSR-3y and OSR-5y, compared to OD CCRT. In addition, BID CCRT had a higher complete response (CR, RR=1.31, 95%CI 1.01-1.70, p=0.04) than OD CCRT. PFS (HR=0.92, 95%CI 0.79-1.07, p=0.29), annual PFS rate, ORR (RR=0.99, 95%CI 0.93-1.05, p=0.72), and AEs for all grades (RR=1.00, 95%CI 0.98-1.01, p=0.57), and grades 3-5 (RR=1.02, 95%CI 0.95-1.09, p=0.60) were similar between the two arms. Conclusions: BID CCRT appears to be better than OD CCRT for limited-stage SCLC, with better antitumor effects (OS, OSR and CR) and similar AEs. However, the high levels of AEs in both arms should be taken as a sign of caution. More large sample and high-quality RCTs need to be conducted to confirm our conclusions.